Maternal Intake of n-3 Polyunsaturated Fatty Acids During Pregnancy Is Associated With Differential Methylation Profiles in Cord Blood White Cells - Bianchi, Marzia; Alisi, Anna; Fabrizi, Marta; Vallone, Cristina; Ravà, Lucilla; Giannico, Riccardo; Vernocchi, Pamela; Signore, Fabrizio; Manco, Melania (Frontiers in Genetics, 2019)
A healthy diet during pregnancy is pivotal for the offspring health at birth and later in life. N-3 polyunsaturated fatty acids (n-3 PUFAs) are not endogenously produced in humans and are exclusively derived from the diet. They are pivotal for the fetus growth and neuronal development and seem beneficial in reducing the risk of cardiometabolic diseases and preventing later allergic disorders in the offspring by modifying the inflammatory immune responses. In the present study, we investigated the association between maternal intake of n-3PUFAs, profiled on cord blood erythrocyte membranes, and offspring DNA methylation on cord blood mononuclear cells in 117 mother-newborn pairs from the “Feeding fetus’ low-grade inflammation and insulin-resistance” study cohort. N-3 PUFA content on erythrocyte membranes is a validated biomarker to measure objectively medium term n-3 PUFA intake. Based on n-3 PUFA distribution in the whole cohorts of mothers, we identified mothers with low (n-3 PUFA concentration <25th percentile), medium (n-3 PUFAs between 25th and 75th percentiles), and high n-3 PUFA content (>75th percentile). The HumanMethylation450 BeadChip (Illumina) was used for the epigenome-wide association study using the Infinium methylation assay. No difference was found in the overall methylation profile. At the intergroup comparison, 8,503 sites had significantly different methylation between low and high n-3 PUFA groups; 12,716 between low and medium n-3 PUFA groups; 18,148 between high and medium n-3 PUFA groups. We found differentially methylated genes that belong prevalently to pathways of signal transduction, metabolism, downstream signaling of G protein-coupled receptors and gene expression among others. Within these pathways, we identified 4 differentially methylated genes, namely MSTN, IFNA13, ATP8B3 and GABBR2, that are involved in the onset of insulin resistance and adiposity, innate immune response, phospholipid translocation across cell membranes; mechanisms of addiction to high fat diet, alcohol and sweet taste. In conclusion, our results suggest that maternal n-3 PUFAs intake during pregnancy has potential to influence the offspring DNA methylation.